UJI AKTIVITAS REPELAN MINYAK ATSIRI JAHE EMPRIT (Zingiber officinale Roxb. “Cochin Ginger”) DAN JAHE MERAH (Zingiber officinale Roxb. var rubrum) DENGAN BASIS MINYAK WIJEN DAN MINYAK KELAPA TERHADAP NYAMUK Aedes aegypti - Sri Mulyani; Reidinda Ratna Puspita Sari; Sitti Rahmah Umniyati (Majalah Obat Tradisional, 2014)
Aedes aegypti is a vector for Dengue. The use of synthetic repellent cause several health issue. Zingiber officinale Roxb. “Cochin Ginger” essential oil (A) and Zingiber officinale Roxb. var rubrum essential oil (B) was used as a repellent for Aedes aegypti. Increasing of repellent activity was strived by formulating A and B with sesame oil and coconut oil as a base. The aim of this study was to compare repellent activity between A and B, to know the influence of oily base to repellent activity of A and B, to know the effective concentration of essential oil in oily base as a repellent.Isolation of essential oil was done by water and steam destilation. Quantitative and qualitative assays by GS-MS. Repellent activity was tested by three steps: initiation, effective consentration assay, and effective concentration of repellent activity. Essential oil on certain concentration (100%, 50% in the base, the effective concentration of SLD) and Lemon grass essential oil was applied on the surface of palm hand. The hand was put into 20x20x20 cm3 cage containing 25 female Aedes aegypti. The number of Aedes aegypti lied on the hand was noted to count protective capacity. First bite was counted as protective time. Analyse was done by One-way ANOVA and Post Hoc Test Tukey HSD (Homogeneous subsets) or Kruskal-Wallis and Mann-Whitney Test.  The result showed that A and B contain camphene, mirsene, 1,8-sineol, l-linalool, l-borneol, neral, geraniol, sitral, and α-kurkumen (only A) that quantitatively different. Statistic result showed that B has a greater repellent activity than A. Sesame oil base give a better effect on repellent activity of sesame oil compare than coconut oil. The effective concentration of Zingiber officinale Roxb. “Cochin Ginger” essential oil and Zingiber officinale Roxb. var rubrum essential oil in sesame oil and coconut oil was 75, 85, 85 and 90%, respectively.